التحديات في دمج تعلم اللغة العربية باستخدام منصة يوتوب: TANTANGAN FILOSOFIS DALAM MENGINTEGRASIKAN PEMBELAJARAN MENGGUNAKAN PLATFORM YOUTUBE DALAM PENGAJARAN BAHASA ARAB - ma'sum, muhammad_ainul_yaqin; Kamal Yusuf (An-Nas, 2025)
This study aims to analyze the philosophical challenges arising from the use of YouTube as a medium for teaching the Arabic language, focusing on the ontological, epistemological, and axiological dimensions. A qualitative descriptive method was employed, utilizing data collection tools such as semi-structured interviews with five teachers and participant observation within classroom settings. The findings reveal that ontologically, YouTube expands the learning space but reduces the intensity of interaction between teacher and student. Epistemologically, the platform accelerates the transmission of knowledge through visual means, although this may result in a superficial understanding and weakened comprehension. Axiologically, core values inherent in religious school environments such as respect, discipline, and patience—may erode in the absence of effective educational supervision. The study concludes that integrating digital media into religious education requires philosophical awareness to balance technological innovation with the preservation of traditional educational values. There is a growing need for pedagogical strategies that harmoniously integrate the benefits of modern technology with the rich educational heritage of religious schools.